2010
DOI: 10.1007/s11033-010-0428-0
|View full text |Cite
|
Sign up to set email alerts
|

The CSN1S1 N and F alleles identified by PCR-SSCP and their associations with milk yield and composition in Chinese dairy goats

Abstract: A method was depicted to identify null allele CSN1S1 N and low allele CSN1S1 F of the CSN1S1 gene of goat using PCR-SSCP (polymerase chain reaction-single strand conformation polymorphism). First, primer A was designed to amplify the exon 9 of CSN1S1 gene which produced three genotypes AA, AB, and BB. Among these three genotypes, only AA and AB individuals had a cytosine deletion at exon 9 after DNA sequencing, which cannot be used to identify the N and F alleles. Therefore, primer B was used to amplify intron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…It means that polymorphisms occurring at a casein locus have to be considered in the context of the casein gene cluster, using information deriving from the entire casein haplotype (Hayes et al, 2006; Finocchiaro et al, 2008). The goats analyzed in this study showed the occurrence of defective alleles at the CSN1S1 locus, coding for αs 1 -casein, such as the F, 01 and N alleles in our previous studies (Yue et al, 2011). Therefore further studies are required to determine the relationship between the absence of CSN1S2 D and CSN1S2 O alleles and the distribution of alleles at CSN1S1 , CSN2 and CSN3 loci in the populations studied.…”
Section: Results and Disussionsupporting
confidence: 55%
See 1 more Smart Citation
“…It means that polymorphisms occurring at a casein locus have to be considered in the context of the casein gene cluster, using information deriving from the entire casein haplotype (Hayes et al, 2006; Finocchiaro et al, 2008). The goats analyzed in this study showed the occurrence of defective alleles at the CSN1S1 locus, coding for αs 1 -casein, such as the F, 01 and N alleles in our previous studies (Yue et al, 2011). Therefore further studies are required to determine the relationship between the absence of CSN1S2 D and CSN1S2 O alleles and the distribution of alleles at CSN1S1 , CSN2 and CSN3 loci in the populations studied.…”
Section: Results and Disussionsupporting
confidence: 55%
“…Furthermore, based on the nucleotide sequence characterization of CSN1S2 B, C and E alleles, the PCR-SSCP procedure was developed for genotyping them by analyzing polymorphisms of exon 9 and exon 16 of CSN1S2 gene (Table 1). The PCR-SSCP and RFLP-PCR procedures were carried out based on Yue et al (2011) and Ramunno et al (2001a) respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The CSN1S1 gene encodes α-s1 casein, one of the proteins constituting milk that can improve calcium uptake in mammals, which affects milk performance and growth development [14,15,23,26]. Many studies have shown that CSN1S1 polymorphisms can affect the milk performance in different goat breeds [19][20][21][22]. Our team has previously identified an 11-bp indel within the CSN1S1 gene, which strongly affected litter size in a large sample of SBWC goats (n = 3047) [1].…”
Section: Discussionmentioning
confidence: 99%
“…Othman et al (2013) observed the prevalence of TT genotype in Egyptian sheep breeds by employing PCR-SSCP method. Polymorphic sites have also been identified in many breeds of goats such as Italian goat Garganica, Spanish breeds and Chinese goat breeds (Ramunno et al 1991;Soares et al 2009;Yue et al 2011).…”
Section: Pcr-rflp Polymorphism Analysismentioning
confidence: 99%